Weterani poszkodowani : rzeczywistość życia po powrocie z misji - Marchewka, Marek (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
This publication is devoted to problems of veterans injured returnees to the country after missions beyond the borders of our state. Polish military missions have existed for over 60 years. It was a total of 80 operations and foreign missions in which participated our soldiers and military personnel. Over those 60 years did not return to the country in 1142 participants, including 22 killed in Iraq and 39 in Afghanistan. The first three Polish soldiers were killed in 1955 in a helicopter crash in Korea. They were using the language of military losses irreversible, but in addition to the dead, we must realize that in the course of carring out their duties in additions to the dead and wounded are also victims who return to the homeland. During the operations in the Middle East were injured 500 Poles. 10 years of Polish participation in the Afghan war victims have been injured and more than 600 injured, 300 seriously injured. What the Polish state mode to compensate former participants of the mission their services abroad, when they became veterans injured. Undoubtedly step facing front of the long term expectations of many victims of the Mission is the Act 19 August 2011 by veterans of activities outside the country, wich is decidated to this publication
Keywords: injured veterans; combat mission; stabilization mission; disabled; Law on Veterans